Conceptual framework. Growing Up in Hungary - Cohort '18 Hungarian birth cohort study - Zsuzsanna Veroszta (Hungarian Demographic Research Institute, 2019)
The Demographic Research Institute of the Hungarian Central Statistical Office launched a birth cohort study entitled 'Growing Up in Hungary - Cohort '18',~ which follows children born in Hungary in 2018 and 2019 on a large nationally representative sample. The main objective of the research program is to provide a comprehensive overview of child development and its influencing factors in Hungary. The conceptual framework of the Cohort '18 study presents the theoretical and methodological background of the research.
Keywords: J12; J13; 300; Cohort '18; birth cohort study; child development; Fertilität; Kinder; Gesundheit; Kohortenanalyse